2011
DOI: 10.2478/v10102-011-0019-5
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids in prevention of diseases with respect to modulation of Ca-pump function

Abstract: Flavonoids, natural phenolic compounds, are known as agents with strong antioxidant properties. In many diseases associated with oxidative/nitrosative stress and aging they provide multiple biological health benefits. Ca2+-ATPases belong to the main calcium regulating proteins involved in the balance of calcium homeostasis, which is impaired in oxidative/nitrosative stress and related diseases or aging. The mechanisms of Ca2+-ATPases dysfunction are discussed, focusing on cystein oxidation and tyrosine nitrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 76 publications
(102 reference statements)
1
25
0
Order By: Relevance
“…In vivo, mice studies have revealed that consumption of GT catechins may decrease the risk of atherosclerosis by improving the bioavailability of NO and by causing vasorelaxation, however, data appeasing this in humans is presently insufficient (Velayutham et al 2008). One study postulated that catechins could be the constituent responsible for their observed improvements in cell viability by reducing the intracellular Reactive Oxygen Species accumulation (Horáková 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, mice studies have revealed that consumption of GT catechins may decrease the risk of atherosclerosis by improving the bioavailability of NO and by causing vasorelaxation, however, data appeasing this in humans is presently insufficient (Velayutham et al 2008). One study postulated that catechins could be the constituent responsible for their observed improvements in cell viability by reducing the intracellular Reactive Oxygen Species accumulation (Horáková 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[9] It is commonly known as scarlet mallow or midday flower in English. In India, decoction of leaves was drunk for inflammatory glands.…”
mentioning
confidence: 99%
“…Many bioactive compounds have been discovered from plants which have flavonoids, natural phenolic compounds, and phytoestrogens are strong antioxidant (Horáková, 2011; Yan et al, 2013). Fruits and vegetables which are enriched with higher content of flavonoid prevents the development of cardiovascular disease (Horáková, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Fruits and vegetables which are enriched with higher content of flavonoid prevents the development of cardiovascular disease (Horáková, 2011). Cardiac hypertrophy is inhibited by different antioxidants caused by ROS (Tsujimoto et al, 2005; Sheng, 2007).…”
Section: Introductionmentioning
confidence: 99%